DAMPAK APLIKASI TIKTOK TERHADAP PERILAKU KEAGAMAAN REMAJA DI DUSUN TUGU, DESA NGROMO, KECAMATAN NAWANGAN, KABUPATEN PACITAN - Novitsa Dwina; Lambang Tendy Ambodo; Novitsa Dwina Kurniaputri; Ummu Khatijah; Winda Ika Riyani (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
The era of globalization has made technology and knowledge more advanced, one of which is social media. So sometimes it makes them unable to judge what is appropriate and inappropriate with various movements regardless of whether it is good or bad for others or for themselves. So, of course this can affect the behavior of teenagers later. The purpose of this study was to determine the impact of the TikTok application on adolescent religious behavior in Tugu Hamlet, Ngromo Village, Nawangan District, Pacitan Regency, East Java. Meanwhile, the method used in this research uses a qualitative approach with case study research methods, data collection techniques through observation and observation. The use of the TikTok application has an impact on adolescent religious behavior, including the negative impacts, namely, delaying the obligatory prayers, making them lazy to recite the Qur'an, and making them lazy to read religious books. A positive impact is also obtained when looking at content related to Islam, because it can create a desire to change to Islamic behavior.Keywords: Tiktok Application; TikTok Impact; Religious Behaviour